Agricultural decisions after relaxing credit and risk constraints - Dean Karlan; Isaac Osei-Akoto; Robert Darko Osei; Christopher Udry (Yale University, Economic Growth Center, 2012)
The investment decisions of small-scale farmers in developing countries are conditioned by their financial environment. Binding credit market constraints and incomplete insurance can reduce investment in activities with high expected profits. We conducted several experiments in northern Ghana in which farmers were randomly assigned to receive cash grants, grants of or opportunities to purchase rainfall index insurance, or a combination of the two. Demand for index insurance is strong, and insurance leads to significantly larger agricultural investment and riskier production choices in agriculture. The salient constraint to farmer investment is uninsured risk: when provided with insurance against the primary catastrophic risk they face, farmers are able to find resources to increase expenditure on their farms. Demand for insurance in subsequent years is strongly increasing in a farmer's own receipt of insurance payouts, and with the receipt of payouts by others in the farmer's social network. Both investment patterns and the demand for index insurance are consistent with the presence of important basis risk associated with the index insurance, and with imperfect trust that promised payouts will be delivered.
Keywords: C93; D24; D92; G22; O12; O13; O16; Q12; Q14; 330; agriculture; insurance markets; credit markets; risk; underinvestment; misallocation; Kleinbauern; Investitionsentscheidung; Liquiditätsbeschränkung; Agrarversicherung; Risikopräferenz; Entwicklungsländer; Ghana